Pertanggungjawaban Hukum Kepolisian Yang Melakukan Kealfaan Dalam Tindakan Diskresi Terhadap Tindak Pidana Lalu Lintas - Apri Amalia; Johannes Mangapul Turnip (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Discretionary actions are the authority of investigators who are decided by the Police in dealing with legal issues ini the field directly and without asking for instructions or decisions from their superiors. The discretion exercised by investigators basically must comply with statutory regulations and the code of ethics for the police profession. However, in reality there is still discrimination in the exercise of police discretion. The aim of the research is to find out the mechanism of impelemntation and legal accountability for the police who do negligence ini traffic discretion. The research method uses normative research conducted using a statutory approach and concepts related to the police. The data used are secondary data ini the form af laws and regulations, books, scientific papers, experts, articles and then these data are processed qualitively. The results of the study show that the mechanism for applying police discretion to traffic crimes at the investigative level is that the police go to the scene of a traffic accident and then make a sketch af the crime scene, help the victim, record witness, secure avidence, the police make a case analysis and exercise discretion in case of an accident, light. The discretionary authority of the police causes investigators to have the authority to make decisions or choose various actions in resolving the law violations they handle. The discretionary authority og the police which is individual in nature is the resolution of traffic accident cases by way of deliberation between the parties involved in the accident. Criminal liabity for negligence by members of the Indonesian National Police is based on article 359 of the Criminal Code, it is proven that the actions of the defendant because of thin negligence caused another person to die is punishable by imprisonment for a maximum of five years of imprisonment for a maximum of one year.